The taxonomy and nomenclature of Kalanchoe ×vadensis [K. blossfeldiana × K. marmorata var. somaliensis] (Crassulaceae subfam. Kalanchooideae), an early nothospecies produced in The Netherlands in the 1950s - Smith, Gideon F. (Phytotaxa, 2022)
The taxonomy and nomenclature of Kalanchoe ×vadensis (Crassulaceae subfam. Kalanchooideae) [hybrid formula: K. blossfeldiana × K. marmorata var. somaliensis], an artificially produced amphidiploid, are discussed and clarified. An amplified description is provided for the nothospecies. The name K. ×vadensis is epitypified.